PELAKSANAAN BALANCED SCORECARD DALAM MENGUKUR KINERJA PEGAWAI (STUDI KASUS PADA PT. PLN SUMBAGUT) - FITHRA MAHARANI; ELWIN KURNIAWAN; NURHADANA . (LP2MTBM MAKARIOZ, 2021)
The purpose of this study is to determine the influence of the implementation of balanced scorecard in measuring employeeperformance in PT. PLN SUMBAGUT. The results prove that the financial perspective can be said to be good becauserevenues have increased, resulting in an effectiveness ratio in 2016 of 90.88% and in 2017 of 97.41% and resulting in anachievement of 83.33%. Customer perspective through improving quality and service, as well as minimizing customercomplaints caused the quantity of goods sent by customers for cargo delivery services to increase by 17% from 100% in2017 and result in an achievement of 98.50%. The internal business process perspective succeeded in creating a fast andquality cargo delivery service process to reduce the number of customer protests to the maximum. Thus, the contribution ofcargo delivery services to operating income increased from Rp.301,950,000,000 in 2016 to Rp.363,400,000,000 or equal toa contribution of 13.21%, and nominal growth of Rp.61.450.000.000 or equal to 20.35% and resulted in an achievement of92.66%.